The Effect of Number of Training Samples for Artificial Neural Network - Tawfiq, L. N. M.; Tawfiq, M. N. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we study the effect of the number of training samples for Artificial neural networks ( ANN ) which is necessary for training process of feed forward neural network .Also we design 5 Ann’s and train 41 Ann’s which illustrate how good the training samples that represent the actual function for Ann’s.